Structural (Super)Plasticity of Magnesium Materials - Zuzanka Trojanova; Zoltan Szaraz; Oksana Padalka; Talant Ryspaev; Pavel Lukac (Communications - Scientific letters of the University of Zilina, 2012)
Superplastic behaviour of two magnesium alloys QE22 and EZ33 having a grain size of 1μm was studied at a temperature of 420 °C and in the strain rate interval from 1 104 to 1 103 s1. The substructure of samples was analysed by the transmission electron microscope before and after deformation. The substructure of samples exhibits an existence of particles in the grain boundaries. These precipitates are very stable even at high deformation temperature and they are reason for the relatively high ductility of alloys. Observed ductility of the WE54/SiCp composite is much lower due to the existence of ceramic particles in the grain boundaries. They inhibit the grain boundary sliding and are the reason for the cavitations and early fracture of the composite.